PERMAINAN DALAM PEMBELAJARAN BAHASA: PELATIHAN KOMPETENSI GURU-GURU BAHASA DI MAN 2 YOGYAKARTA - Sudarmaji Sudarmaji; Iman Santoso; Retna Endah Sri Mulyati; Isti Haryati; Diyan Fatimatuz Zahro (LPPM ITB AAS Indonesia Surakarta, 2023)
The training for language teachers aims to improve the competence of) language teachers in teaching a language in the classroom. By participating in this training, language teachers are expected to be more familiar with games in language teaching and apply them in the classroom so that students' ability to learn languages include foreign language will also increase. The method used is training that is carried out offline and online in three meetings. In the first meeting, language teachers were guided to understand the concept of games in language and foreign language teaching. The second meeting was filled with best practice presentations and practical discussions on making a Learning Implementation Plan by utilizing games in language teaching. In the third session, the participants presented their lesson plans and learning videos from their classrooms. From the results of the training, it is known that after attending the training, language teachers' understanding and mastery of various games in language teaching and learning have increased. Teachers are also ready to apply games in their classrooms. Keywords: Games, language learning, training Abstrak Pelatihan permainan dalam pembelajaran bahasa bagi guru-guru bahasa bertujuan untuk meningkatkan kompetensi guru-guru bahasa dalam pembelajaran bahasa di kelas. Dengan mengikuti pelatihan ini diharapkan guru-guru bahasa lebih mengenal permainan dalam pembelajaran bahasa dan mengaplikasikannta di kelas sehingga kemampuan siswa dalam belajar bahasa termasuk bahasa asing juga semakin meningkat. Metode yang dipakai adalah pelatihan yang dilaksanakan secara luring dan daring dalam tiga kali pertemuan. Pada pertemuan pertama, para pengajar bahasa dibimbing untuk memahami konsep permainan dalam pengajaran bahasa asing. Pertemuan kedua diisi dengan presentasi best practice dan diskusi praktik membuat Rencana Pelaksanaan Pembelajaran dengan memanfaatkan permainan dalam pembelajaran bahasa. Sesi ketiga, para peserta mempresentasikan RPP dan video pembelajaran. Dari hasil pelatihan diketahui bahwa setelah mengikuti pelatihan, pemahaman dan penguasaan guru-guru bahasa tentang berbagai permanan dalam pembelajaran bahasa semakin meningkat. Guru-guru juga siap untuk mengaplikasikan permainan dalam pembelajaran bahasa di kelasnya. Kata kunci: pelatihan, pembelajaran bahasa, permainan